Counseling on Eradication Strategy Poverty Based on Digital Literacy in Nagrak Village, Buahdua District, Sumedang - Fauzobihi, Fauzobihi; Yuda, Panji Syafari; Ramadhina, Retno (Abdi Masyarakat, 2024)
Poverty is a state in which a person cannot fulfill their basic needs such as food, clothing, shelter, education, and medical care. Micro, small, and medium enterprises (MSMEs) are business activities that have the ability to increase employment, encourage economic growth, and increase community income. However, in the current digital era, there are still many MSMEs that are still stuttering with technology, which has hampered MSMEs from growing and developing. The purpose of this study was to determine and analyze the extension of digital literacy-based poverty alleviation strategies in Nagrak Village, Buahdua District, Sumedang . This research method uses qualitative methods. The data collection techniques used are interviews, observation, and documentation techniques. By increasing the competitiveness of MSMEs through digital literacy regarding digital marketing techniques, marketplace elements, and MSME branding. It is expected that the growth and development of MSMEs in Nagrak Village can make a significant positive contribution to poverty alleviation.